Long-term clinical effects of epalrestat, an aldose reductase inhibitor, on progression of diabetic neuropathy and other microvascular complications: multivariate epidemiological analysis based on patient background factors and severity of diabetic neuropathy - Hotta, N (Blackwell Publishing Ltd, 2012)
AIMS: The goal of the study was to evaluate the efficacy of epalrestat, an aldose reductase inhibitor, on diabetic retinopathy and diabetic nephropathy, based on analysis of the results of the Aldose Reductase Inhibitor–Diabetes Complications Trial, a 3-year multicentre comparative clinical trial of conventional therapy (control group) and epalrestat therapy (epalrestat group) in Japanese patients with mild diabetic neuropathy. METHODS: The subjects of the study were patients enrolled in the Aldose Reductase Inhibitor–Diabetes Complications Trial for whom data for major patient characteristics, severity of diabetic neuropathy at the end of the study and time-courses of diabetic retinopathy and diabetic nephropathy were available (57 and 52 patients from the control and epalrestat groups, respectively). Progression of diabetic retinopathy/nephropathy (a primary endpoint) in relation to major patient characteristics, severity of diabetic neuropathy at the end of the study (assessed from the mean of z-scores in four neurological function tests) and epalrestat treatment were analysed using univariate analysis and multiple logistic regression analysis. RESULTS: Progression of diabetic retinopathy/nephropathy was significantly inhibited in the epalrestat group compared with the control group (odds ratio = 0.323, P = 0.014) and was dependent on the severity of diabetic neuropathy at the end of the study (odds ratio = 2.131, P = 0.025). CONCLUSIONS: Epalrestat prevented progression of diabetic neuropathy and retinopathy/nephropathy. The effect on diabetic retinopathy/nephropathy may have occurred indirectly because of the prevention of progression of diabetic neuropathy, in addition to the inhibitory action of epalrestat on aldose reductase.